Hemangiossarcoma na base do átrio esquerdo de um cão com degeneração da válvula mitral e tricúspide – relato de caso - Fiorini, Emiliana Andrades (2017)
Hemangiosarcoma (HSA) is a malignant neoplasm originating from the vascular endothelium, with high metastatic power and commonly described in the spleen, liver, and right atrium. Thus, the objective of the present study is to report the occurrence of HSA at the base of the left atrium of a male, elderly, Lhasa Apso dog, treated with cyanosis, orthopedic position, cough. In the physical examination, the presence of crackling was observed in pulmonary lobes, murmur in focus of mitral and tricuspid grade IV\VI. The recommended emergency therapy was performed until the clinical improvement of the animal. After echocardiography, mitral and tricuspid valvular degeneration was confirmed, as well as the presence of an irregular, mixed echocardiogram, extra-cardiac, immobile at the base of the left atrium, measuring 2.9 x 1.44 cm in diameter. The clinical therapy established stabilized the clinical picture for 128 days, with recurrence of pulmonary edema and severe hemorrhagic pleural effusion, with the owners opting for euthanasia of the animal and necropsy confirming the definitive diagnosis of extrahepatic SAH at the base of the left atrium.